Helping Haiti's transportation issues: Increasing Haiti's medical liabilities - Nancy McLaughlin; Hannah Rogers (Edinburgh University Global Health Society, 2013)
Haiti has experienced an explosion of the use of motorcycles by young, inexperienced drivers fueled by the departure of aid workers leaving them behind after assisting with disaster relief. The consequence is a strain on Haiti's already fragile medical system due to the overwhelming number of traumas presenting for treatment. The motorcycles have become an indispensible form of transportation but lack of governmental oversight predisposes an environment that is primed to strain the country's already limited medical assets.